2004
DOI: 10.5367/0000000042530178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Application on Leaf Yield and Nutritive Quality of Black Nightshade (Solanum Nigrum L.)

Abstract: Two experiments were carried out to investigate the effects of nitrogen application and plant age on edible leaf yield and anti-nutrient content of Solanum nigrum plants. Nitrogen rates were 0, 26, 52, 78 and 104 kg ha-1 , applied in one, two or three applications. Shoots were harvested fortnightly starting at eight weeks up to 20 weeks after transplanting. Edible leaf yield increased with both increasing nitrogen application rates and plant age. Plant age significantly affected the oxalate content. In Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…Low N rate was found to be optimum for maximum growth of B. alba during the early planting season. is agrees with [36] who reported that N application promoted leaf and stem production but increased vegetative growth but plateaued at an optimum N rate [9,37]. is is because the absorption and translocation of mineral nutrients by plants from the soil are influenced by soil and air temperatures.…”
Section: Discussionsupporting
confidence: 89%
“…Low N rate was found to be optimum for maximum growth of B. alba during the early planting season. is agrees with [36] who reported that N application promoted leaf and stem production but increased vegetative growth but plateaued at an optimum N rate [9,37]. is is because the absorption and translocation of mineral nutrients by plants from the soil are influenced by soil and air temperatures.…”
Section: Discussionsupporting
confidence: 89%
“…Dry mass production was affected by N level (Table 2), in line with finding by Opiyo (2004). Fruit load as represented by the ratio dry mass of fruit to leaf was the highest in plants of 0 kg N ha -1 at 6 WAP, and 60 kg N ha -1 at 12 WAP.…”
Section: Dry Matter Production and Its Partitioningsupporting
confidence: 82%
“…It has also been reported that in many parts of western Kenya P stress is a major limiting nutrient and also the response of other nutrients is usually inhibited under this limitation (Opiyo 2004). Phosphorus efficiency of the identified variety P-224 was probably due to its genetic ability to produce high yield per unit P acquired.…”
Section: Discussionmentioning
confidence: 94%